2016
DOI: 10.1002/14651858.cd011272.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin and rapalogs for tuberous sclerosis complex

Abstract: We found evidence that oral everolimus significantly increased the proportion of people who achieved a 50% reduction in the size of sub-ependymal giant cell astrocytoma and renal angiomyolipoma. Although we were unable to ascertain the relationship between the reported adverse events and the treatment, participants who received treatment had a similar risk of experiencing adverse events as compared to those who did not receive treatment. Nevertheless, the treatment itself significantly increased the risk of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 92 publications
1
76
0
4
Order By: Relevance
“…The mTOR enzyme is the master switch for cellular growth or destruction . Inhibition of mTOR is effective in halting disease processes related to cellular proliferation and has been widely used to inhibit B‐ and T‐cell activation to avoid posttransplant rejection . Although many studies have focused on the role of PI3K activation and inhibition in vascular endothelial cells, it is important to keep in mind that sirolimus is an immunosuppressant, and it may have greater than one mechanism of action in LM.…”
Section: Therapy For Head and Neck Lymphatic Malformations Based On Mmentioning
confidence: 99%
“…The mTOR enzyme is the master switch for cellular growth or destruction . Inhibition of mTOR is effective in halting disease processes related to cellular proliferation and has been widely used to inhibit B‐ and T‐cell activation to avoid posttransplant rejection . Although many studies have focused on the role of PI3K activation and inhibition in vascular endothelial cells, it is important to keep in mind that sirolimus is an immunosuppressant, and it may have greater than one mechanism of action in LM.…”
Section: Therapy For Head and Neck Lymphatic Malformations Based On Mmentioning
confidence: 99%
“…In the absence of such a study, in TSC patients, clinicians have to follow the best evidence published so far, regarding the selection of a specific drug. In a very recent systematic review, authors concluded that oral everolimus has high-quality evidence regarding its effect in reducing the size of SEGA and adult renal angiomyolipomas, without significantly increasing the risk of patients to experience adverse events, as compared to those not receiving any treatment [69]. However, the usage of the drug seems to increase the risk of dose reduction, interruption, or withdrawal, over time [69].…”
Section: Current Therapeutic Challenges Using Mtor Inhibitorsmentioning
confidence: 99%
“…In a very recent systematic review, authors concluded that oral everolimus has high-quality evidence regarding its effect in reducing the size of SEGA and adult renal angiomyolipomas, without significantly increasing the risk of patients to experience adverse events, as compared to those not receiving any treatment [69]. However, the usage of the drug seems to increase the risk of dose reduction, interruption, or withdrawal, over time [69]. The existence of a sirolimus topical formulation makes it attractive for the treatment of skin manifestations of TSC, more than the systemic everolimus intake.…”
Section: Current Therapeutic Challenges Using Mtor Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…DOI: 10.1111/bjd.16397 DEAR EDITOR, The use of topical rapamycin or rapalog, a mammalian target of rapamycin inhibitor, has shown promising results in treating facial angiofibromas (FAs) in children with tuberous sclerosis complex. [1][2][3][4][5][6][7] Nevertheless, several issues remain: the effectiveness, stability and tolerability of the ingredients, and the costthe higher the concentration of rapamycin the more expensive the product.…”
mentioning
confidence: 99%